Protective Effect of Melatonin for Renal Ischemia-Reperfusion Injury: A Systematic Review and Meta-Analysis - Dun, Rong-liang; Lan, Tian-ying; Tsai, Jennifer; Mao, Jian-min; Shao, Yi-qun; Hu, Xiao-hua; Zhu, Wen-jing; Qi, Guang-chong; Peng, Yu (Frontiers in Physiology, 2022)
Background: Renal ischemia-reperfusion (I/R) injury is the most common cause of acute kidney injury (AKI). Melatonin has been shown as a powerful antioxidant, with many animal experiments have been designed to evaluate the protective effect of melatonin in renal I/R injury. Objectives: This systematic review aimed to assess the protective effect of melatonin on renal I/R injury in animal experiments. Methods and Results: The PubMed, Embase, Web of Science, and Science Direct databases were searched for animal experiments applying melatonin to treat renal I/R injury to February 2021. 31 studies were included. The pooled analysis showed a greater reduction of blood urea nitrogen (BUN) (21 studies, weighted mean difference (WMD) = -30.00 [-42.09 to -17.91], p < 0.00001), and serum creatinine (SCr) (20 studies, WMD = -0.91 [-1.17 to -0.66], p < 0.00001) treated with melatonin. Subgroup analysis suggested that multiple administration could reduce the BUN compared with control. Malondialdehyde and myeloperoxidase were significantly reduced, meanwhile, melatonin significantly improved the activity of superoxide dismutase, and glutathione. The possible mechanism for the protective effect of melatonin in renal I/R injury is inhibiting endoplasmic reticulum stress, apoptosis, inflammation, autophagy, and fibrillation in AKI to chronic kidney disease. Conclusions: From the available data of small animal studies, this systematic review demonstrated that melatonin could attenuate renal I/R injury through improving renal function and antioxidative effects, then multiple administration of melatonin might be more appropriate. Nonetheless, extensive animal studies and well-designed randomized controlled trials are needed further to confirm the protective effect of melatonin.